Development of performance standard for circular ducting local exhaust ventilation system at workplace - Hasan, Nor Halim (UTeM, 2016)
Engineering controls, such as local exhaust ventilation (LEV) system, are functioned to remove contaminants from work place, as it is vital that the level of contaminants must comply with legislation. Furthermore, LEV in industries has been designed, fabricated, and monitored to perform better in accordance to the American Conference for Governmental Industrial Hygienists (ACGIH) standard and the Guideline on LEV provided by Department of Occupational Safety and Health (DOSH). This study on LEV had been depicted from the Industrial Hygiene Technician assessment report due to issues on the effectiveness of LEV to remove contaminants. That includes problem of assessing, measuring the fan area, as well as the material fabricated. Thus, the objective of the study was to identify the current compliance of the national law with regards to LEV system. Moreover, besides determining the usage of ducting in LEV by looking into the characteristics of the material using American Society for Testing and Materials (ASTM) standard, the performance of LEV system was tested, as suggested in the ACGIH standard, through design, construct, and measurement data. Three different models (in laboratory scale model) of LEV system were designed according to the ACGIH Standard, and tested to determine the relationship between analytical, experimental, and numerical analyses in this study. As for the three models, they were designed and fabricated to measure velocity and flow of air. Meanwhile, as for numerical analysis, computer simulation i.e. Ansys CFX, Engineering Simulation Software version 14.0 (Ansys 14.0) was used to simulate these three models for verification and comparison. A comparative study was conducted to retrieve analytical, experimental, and simulation results to justify the performances of LEV on different velocity and static pressure values. The results showed that there was insignificant difference between the values of velocity that were calculated, measured, and simulated. The average difference for velocity data was 8%. Static pressure for analytical and experimental results also portrayed insignificant difference compared to simulation that was mostly influenced by the mesh of variable setting. The outcome of the study was to produce the Malaysian Standard on LEV system design, fabrication, measurement, and maintenance. The development of LEV Malaysian Standard through Standard and Industrial Research Institute of Malaysia (SIRIM) Berhad that proposes the evaluation of LEV performance should be carried out before any LEV system is developed due to cost consideration, besides benefiting employees and employers for their safety and health, and in preventing occupational diseases in the future.